2003
DOI: 10.1183/09031936.03.00013003
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of air pollution on daily asthma emergency room admissions

Abstract: Many time-series studies have shown positive associations between air pollutants and asthma morbidity. However, few studies have included pollen as a potential confounder when examining this relationship.This study analysed the short-term association between air pollutants (sulphur dioxide (SO 2 ), particles measured with a median aerodynamic diameter of v10 mm (PM10), nitrogen dioxide (NO 2 ) and ozone (O 3 )) and asthma emergency room admissions in Madrid, Spain, in 1995-1998, adjusting for four types of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 50 publications
9
121
1
7
Order By: Relevance
“…Segala et al 60 in Paris, Atkinson et al 61 in London, and Sunyer et al 33 in the cities of Birmingham, London, Milan, Paris, Rome, Stockholm, and in the Netherlands, associated SO 2 with visits to the emergency departments. In contrast, studies performed in Madrid, 62 Rome 30 and Valencia 63 found no relationship between SO 2 and the hospital admissions for asthma. In Lisbon, repercussion on respiratory diseases among children occurred with delay of only 1-day, which could be explained by the direct effect of SO 2 on the smooth muscle or via sensory afferent nerve fibres that cause reflex bronchoconstriction.…”
Section: Resultsmentioning
confidence: 73%
“…Segala et al 60 in Paris, Atkinson et al 61 in London, and Sunyer et al 33 in the cities of Birmingham, London, Milan, Paris, Rome, Stockholm, and in the Netherlands, associated SO 2 with visits to the emergency departments. In contrast, studies performed in Madrid, 62 Rome 30 and Valencia 63 found no relationship between SO 2 and the hospital admissions for asthma. In Lisbon, repercussion on respiratory diseases among children occurred with delay of only 1-day, which could be explained by the direct effect of SO 2 on the smooth muscle or via sensory afferent nerve fibres that cause reflex bronchoconstriction.…”
Section: Resultsmentioning
confidence: 73%
“…Controlling for other pollutants lowers the effect estimates at times, and at other times makes them statistically insignificant [27]. In some studies, NO 2 , rather than PM, was found to be associated with asthma hospital admissions [28]. An effect of NO 2 has been noted in most panel studies evaluating aggravation of asthma in children, showing a clear effect of NO 2 on incidence of viral infections among asthmatics [29].…”
Section: Nomentioning
confidence: 99%
“…The risk of health problems related to air pollution has been previously reported (Li et al 2013;Wang et al 2013). Air pollution has a substantial influence on health, including reduced pulmonary function and increased mortality and hospital admissions (Dockery et al 1993;Anderson et al 1997;Abbey et al 1999;Peters et al 1999;Linn et al 2000;Galan et al 2003;Tsai et al 2003;Nafstad et al 2004;Fung et al 2005;Peacock et al 2011). For example, a previous study reported that the mortality rate for all diseases increased by 0.55% and the mortality rate associated with pulmonary disease increased by 1.91% secondary to exposure of 10 μg/m 3 of PM 2.5 (Samoli et al 2013).…”
Section: Introductionmentioning
confidence: 99%